Global patents limits of transnational enforcement - Trimble, Marketa (Oxford : Oxford University Press, 2012)
This text explains why a 'global patent' does not exist. It identifies the barriers to its creation from both historical and current perspectives, and discusses the difficulties that arise as inventors, investors, and businesses strive to protect their inventions in the widest territory possible.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Patent laws and legislation; Intellectual property